2021
DOI: 10.1002/pbc.29135
|View full text |Cite|
|
Sign up to set email alerts
|

A scoping review of transition interventions for young adults with sickle cell disease

Abstract: Standardized programming for individuals with sickle cell disease (SCD) transitioning from pediatric to adult-centered care does not currently exist, resulting in high rates of mortality and morbidity. This scoping review examines and evaluates the current literature on SCD transition programs and interventions. Eligible studies described an existing program for individuals with SCD aged 12-29 years preparing to transition.The Evidence Project risk-of-bias tool was used to assess article quality. We identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Previous efforts in improving transition programs have been focusing on patient education to build patient transition preparedness 28,29. A scoping review of transition interventions for young adults with SCD identified over 20 published articles, the majority of which focus on improving patients’ skills and disease knowledge 30. Without acknowledging or addressing the outer and inner setting environment, these programs may not achieve maximum outcomes as desired.…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts in improving transition programs have been focusing on patient education to build patient transition preparedness 28,29. A scoping review of transition interventions for young adults with SCD identified over 20 published articles, the majority of which focus on improving patients’ skills and disease knowledge 30. Without acknowledging or addressing the outer and inner setting environment, these programs may not achieve maximum outcomes as desired.…”
Section: Discussionmentioning
confidence: 99%
“…23 and OpenGrey from their inception to November 2021 supplemented database searches. Third, reference lists of included studies and systematic review [18][19][20][21] also provided sources for studies not identified in the database searches. The 3-step search strategy was implemented by one reviewer (B.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reviews have focused on specific psychological, 18 medication adherence, 19 transition programmes 20 and e‐health interventions, 21 and assessed their effects on particular outcomes. No systematic review has been identified that focused on all types of self‐management interventions for CYP with SCD and included the full range of health and social outcomes that have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Transition of care has generally been defined as a “purposeful, planned process involved in the movement of older children from a focus on pediatric life skills to adult life skills.”14 Research on the core components of and metrics to measure successful transition in SCD is ongoing 15,16. A multinational taskforce of SCD experts recommended specific priorities for SCD-specific transition: skills transfer, increasing self-efficacy, coordination, knowledge transfer, linking to adult services, and evaluating readiness 17.…”
mentioning
confidence: 99%
“…14 Research on the core components of and metrics to measure successful transition in SCD is ongoing. 15,16 A multinational taskforce of SCD experts recommended specific priorities for SCD-specific transition: skills transfer, increasing self-efficacy, coordination, knowledge transfer, linking to adult services, and evaluating readiness. 17 These tasks require skills that may be affected by social, educational, neurocognitive, and structure of care challenges for individuals with SCD.…”
mentioning
confidence: 99%